The Influence of Self-Efficacy, Work–Life Balance, and Job Satisfaction on Employee Performance - Isa Tamala; Audita Nuvriasari (LifeSciFi, 2026)
Employee performance plays a vital role in organizational effectiveness, yet it may decline due to low self-efficacy, poor work–life balance, and inadequate job satisfaction, therefore, this study aims to analyze the influence of self-efficacy, work-life balance, and job satisfaction on employee performance. This research employed a quantitative approach with a saturated sampling technique involving 83 employees, with data collected through questionnaires and analyzed using instrument testing, classical assumption tests, multiple linear regression analysis, t-tests, and the coefficient of determination (R²). The findings reveal that self-efficacy, work–life balance, and job satisfaction have positive and significant effects on employee performance, where self-efficacy enhances confidence and task accomplishment, work–life balance supports productivity through emotional well-being, and job satisfaction emerges as the most dominant factor related to compensation, work relationships, and career development. The adjusted R² value of 0.855 indicates that 85.5% of the variation in employee performance is explained by the three variables, suggesting that improving these factors is essential for enhancing overall performance.